Environmentally relevant concentrations of silver nanoparticles diminish soil microbial biomass but do not alter enzyme activities or microbial diversity - Montes de Oca-Vásquez, Gabriela; Solano-Campos, Frank; Vega-Baudrit, José R; López-Mondéjar, Rubén; Odriozola, Iñaki; Vera, Alfonso; Moreno, José L; Bastida, Felipe (Journal of hazardous materials, 2020)
The increasing use of silver nanoparticles (AgNPs) due to their well-known antimicrobial activity, has led to their accumulation in soil ecosystems. However, the impact of environmental realistic concentrations of AgNPs on the soil microbial community has been scarcely studied. In this work, we have assessed the impact of AgNPs, that mimic real concentrations in nature, on tropical soils cultivated with Coffea arabica under conventional and organic management systems. We evaluated the biomass, extracellular enzyme activities, and diversity of the soil microbial community, in a microcosm experiment as a function of time. After seven days of incubation, we found an increase in microbial biomass in an AgNPs-concentration-independent manner. In contrast, after 60-day-incubation, there was a decrease in Gram+ and actinobacterial biomass, in both soils and all AgNPs concentrations. Soil physico-chemical properties and enzyme activities were not affected overall by AgNPs. Regarding the microbial community composition, only some differences in the relative abundance at phylum and genus level in the fungal community were observed. Our results suggest that environmental concentrations of AgNPs affected microbial biomass but had little impact on microbial diversity and may have little effects on the soil biogeochemical cycles mediated by extracellular enzyme activities.
Keywords: ureasa; kovové nanočástice; Acid Phosphatase; Biomass; beta-glukosidasa; Soil Pollutants; Silver; bakteriální geny; RNA, Ribosomal, 16S; látky znečišťující půdu; Enzyme activities; beta-Glucosidase; Microbiota; Ag nanoparticles; Metal Nanoparticles; Urease; půdní mikrobiologie; mikrobiota; kyselá fosfatasa; Bacteria; Soil Microbiology; Soil microbial community; Genes, Bacterial; biomasa; RNA ribozomální 16S; stříbro